PEACE AND HUMANITY ACCORDING TO HINDU SCRIPTURE - I Ketut Donder (INTERNATIONAL JOURNAL ON HINDU CULTURE, 2023)
Peace and Humanity are two Divine properties among uncountable qualities of God. Even though, peace and Humanity own of God, but every human being has potential nature of peace and Humanity as two natural’s Divine qualities inherent in every one. So, who anyone has no any qualities of divine in his-self, then he will never reach of the peace and has not humanity. The core of peace and humanity are existence of qualities the divine natures in man, in Hindu glossary it called Atma consciousness in man, which is equal mean with God consciousness in man. Few among of the divine qualities, should be exist in man to build the peace and human values, those are keep of satya (truth), follow the Rtam (nature law), follow the dharma (rule), love all being, serve all being, ahimsa or nonviolence, respect to all creation. Therefore Satya Narayana say: In our day-to-day life, if we use the intelligence to discriminate between right and wrong, and follow the dictates of the Atman, then everything will be right. This is the Divine prescription and panacea for life. What is therefore required first is faith in the existence and supremacy of Atman (Satya Narayana in Desai, 2005: 78).